Sistem Pendukung Keputusan Menentukan Karyawan Kontrak Menjadi Karyawan Tetap dengan Algoritma Regresi Linear Berganda - Anak Agung Made Krisna Astrawan,; I Ketut Gede Suhartana, (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2023)
This study aims to aid in decision-making for determining the employment status of contract employees versus permanent employees using the Multiple Linear Regression algorithm. The analysis shows that the independent variables, including Work Experience (X1), Education Length (X2), and Attendance (X3), strongly influence the dependent variable of Employee Status (Y). With a coefficient of determination of 0.734, the model explains 73.4% of the variation in Employee Status based on these variables. The integrated decision support system facilitates decision-making by providing recommendations based on user inputs. Application testing confirms the system's effectiveness in assisting decisions regarding the eligibility of contract employees for permanent employment. Overall, this research contributes to informed and accurate decision-making in employee status determination.
Keywords: Decision Support System, Multiple Linear Regression